Mathematical Modeling Using Multivariate Statistics-(Factor Analysis and Multiple Linear Regression Model): Determinants of Equity Shares of Companies Listed at BSE - Sivarethinamohan, R. (Indian Journal of Finance, 2009)
Equity shares are different from traditional investment products. Investment in equity is subject to market risks. The share prices may fluctuate based on the performance of the company and factors influencing the capital market. This paper highlights how well financial fundamentals are deciding the share prices and to what extend they influence on investors' earnings. The study is based on data collected through directory of the Bombay stock exchange and the Electronic Data base PROWESS provided by Center for Monitoring Indian economy (CMIE).